Studi pendahuluan genetika populasi ikan tuna sirip kuning (thunnus albacares) dari dua populasi di laut Kepulauan Maluku, Indonesia - Nebuchad Nezzar Akbar; Dian Pertiwi; Neviaty P. Zamani; Beginer Subhan; Hawis H. Madduppa (Faculty of Marine and Fisheries, Universitas Syiah Kuala, 2020)
Abstract. Yellowfin tuna (Thunnus albacares) is a large pelagic fish that have high economic value and inhabits the Moluccas Sea, Indonesia. Tuna catches in the Moluccas sea was very high and might decrease the yellowfin tuna population in this region. The research on population genetic of yellowfin tuna is fundamental to answer the problem. This information can be used as baseline data for future management, utilization, and basis of genetic conservation. The objective of this research was to infer the genetic population structure of two populations (North Maluku and Ambon) in the Moluccas Sea, Indonesia. In total, 41 tissue samples from pectoral fins of yellowfin tuna were collected in this study (North Maluku 33 samples and Ambon 8 samples). The results showed that genetic distances were low between the two populations. Additionally, the comparison of genetic distance between the Moluccas population and Indian Ocean waters also showed no significant differences. The Fst analysis showed the high gene flow between these two populations. Furthermore, haplotype network analysis showed that these two populations were the panmixia population. The overall result showed that no refraction genetic in the yellowfin tuna population from two populations in the Moluccas Sea.Keywords: Haplotype, genetic distance, Moluccas Sea, index fixation analysis, yellowfin tuna, population genetic structure. Abstrak. Tuna sirip kuning (Thunnus albacares) merupakan jenis pelagis besar bernilai ekonomis tinggi yang hidup di perairan Laut Maluku, Indonesia. Tangkapan ikan tuna di Laut Maluku berstatus tinggi, sehingga dapat menurunkan jumlah populasi. Penelitian tentang genetika populasi ikan tuna sirip kuning penting dilakukan untuk menjawab permasalahan ini. Informasi ini dapat menjadi sumber data untuk pengelolaan, pemanfaatan dan pelestarian untuk konservasi genetik. Tujuan penelitian untuk mengetahui struktur populasi genetik pada dua populasi di Laut Maluku (Maluku Utara dan Ambon). Secara total, 41 sampel jaringan dari sirip pectoral Tuna sirip kuning dikumpulkan dalam penelitian ini (Maluku Utara 33 sampel dan Ambon 8 sampel). Hasil penelitian menemukan jarak genetik yang dekat antar kedua populasi. Perbandingan jarak genetik pada populasi Perairan Maluku dan Samudera Hindia tidak menunjukan perbedaan signifikan. Analisis fiksasi indeks (Fst) memperlihatkan aliran genetik kuat antar populasi. Analisis jaringan haplotipe menunjukan kedua populasi merupakan populasi panmiksia. Penelitian ini secara umum menunjukkan belum terjadi perubahan struktur genetik populasi ikan tuna sirip kuning pada dua populasi di Laut Maluku.Kata kunci: Haplotipe, jarak genetik, Laut Maluku, analisis fiksasi indeks, tuna sirip kuning, struktur populasi genetik.